From Pioneering Discoveries to Innovative Therapies: A Journey Through the History and Advancements of Nanoparticles in Breast Cancer Treatment - Basingab FS; Alshahrani OA; Alansari IH; Almarghalani NA; Alshelali NH; Alsaiary AH; Alharbi N; Zaher KA (Breast Cancer: Targets and Therapy)
Fatemah S Basingab,1,2 Omniah A Alshahrani,1 Ibtehal H Alansari,1 Nada A Almarghalani,1 Nada H Alshelali,1 Abeer Hamad Alsaiary,3 Najwa Alharbi,4 Kawther A Zaher2,5 1Department of Biological Sciences, Faculty of Science, King Abdulaziz University, Jeddah, 21859, Saudi Arabia; 2Immunology Unit, King Fahd Medical Research Center, King Abdulaziz University, Jeddah, 21859, Saudi Arabia; 3Biology Department, College of Sciences, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 4Department of Biology Science, Faculty of Science, King Abdulaziz University, Jeddah, 21859, Saudi Arabia; 5Department of Medical Laboratory Sciences, Faculty of Applied Medical Sciences, King Abdulaziz University, Jeddah, 21859, Saudi ArabiaCorrespondence: Fatemah S Basingab, Email fbaseqab@kau.edu.saAbstract: Nanoparticle technology has revolutionized breast cancer treatment by offering innovative solutions addressing the gaps in traditional treatment methods. This paper aimed to comprehensively explore the historical journey and advancements of nanoparticles in breast cancer treatment, highlighting their transformative impact on modern medicine. The discussion traces the evolution of nanoparticle-based therapies from their early conceptualization to their current applications and future potential. We initially explored the historical context of breast cancer treatment, highlighting the limitations of conventional therapies, such as surgery, radiation, and chemotherapy. The advent of nanotechnology has introduced a new era characterized by the development of various nanoparticles, including liposomes, dendrimers, and gold nanoparticles, designed to target cancer cells with remarkable precision. We further described the mechanisms of action for nanoparticles, including passive and active targeting, and reviewed significant breakthroughs and clinical trials that have validated their efficacy. Current applications of nanoparticles in breast cancer treatment have been examined, showcasing clinically approved therapies and comparing their effectiveness with traditional methods. This article also discusses the latest advancements in nanoparticle research, including drug delivery systems and combination therapy innovations, while addressing the current technical, biological, and regulatory challenges. The technical challenges include efficient and targeted delivery to tumor sites without affecting healthy tissue; biological, such as potential toxicity, immune system activation, or resistance mechanisms; economic, involving high production and scaling costs; and regulatory, requiring rigorous testing for safety, efficacy, and long-term effects to meet stringent approval standards. Finally, we have explored emerging trends, the potential for personalized medicine, and the ethical and social implications of this transformative technology. In conclusion, through comprehensive analysis and case studies, this paper underscores the profound impact of nanoparticles on breast cancer treatment and their future potential.Keywords: Nanoparticles, Breast Cancer, Targeted Therapy, Drug Delivery, Immunotherapy